2003
DOI: 10.1128/iai.71.9.5273-5279.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody Directed against aCandida albicansCell Wall Mannoprotein Exerts Three Anti-C. albicansActivities

Abstract: Antibodies are believed to play a role in the protection against Candida albicans infections by a number of mechanisms, including the inhibition of adhesion or germ tube formation, opsonization, neutralization of virulence-related enzymes, and direct candidacidal activity. Although some of these biological activities have been demonstrated individually in monoclonal antibodies (MAbs), it is not clear if all these anti-C. albicans activities can be displayed by a single antibody. In this report, we characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 35 publications
(23 reference statements)
4
128
0
6
Order By: Relevance
“…Such findings were described for C. albicans [26] and C. neoformans infection [27]. Moragues et al [26] characterized an mAb against a mannoprotein with a mass4200 kDa on the cell wall of C. albicans with direct candidacidal activity.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Such findings were described for C. albicans [26] and C. neoformans infection [27]. Moragues et al [26] characterized an mAb against a mannoprotein with a mass4200 kDa on the cell wall of C. albicans with direct candidacidal activity.…”
Section: Discussionmentioning
confidence: 73%
“…Such findings were described for C. albicans [26] and C. neoformans infection [27]. Moragues et al [26] characterized an mAb against a mannoprotein with a mass4200 kDa on the cell wall of C. albicans with direct candidacidal activity. Human antibodies against glucosylceramide from C. neoformans inhibited cell budding and fungal growth probably by interfering with the biosynthesis and organization of the cell-wall polymers [27].…”
Section: Discussionmentioning
confidence: 73%
“…On closer examination, however, in at least one case, T H 2-derived antibodies have a protective effect by somehow augmenting cell-mediated immunity 39 . In other cases, antibodies can function as opsonins, promoting fungal ingestion and even killing by phagocytes, and several antibodies are directly fungicidal [40][41][42][43][44][45][46][47] (TABLE 1). These kinds of activities are complementary, rather than exclusive, to cell-mediated mechanisms.…”
Section: Evidence For Protective Antibodies Against Fungal Diseasementioning
confidence: 99%
“…The monoclonal antibody C7 (REF. 44) protects mice against candidiasis 80 apparently by mechanisms similar to antibodies specific for anti-mannotriose. In addition, however, C7 directly inhibits the growth of C. albicans, but by unknown mechanisms 44 .…”
Section: Mechanisms Of Antibody Protectionmentioning
confidence: 99%
“…An IgM MAb C7 that reacts with Als3p and enolase of C. albicans cell wall exerted three anti-candida actions such as candidacidal activity and inhibition of both adhesion and filamentation [77]. Subsequently it was found that the candidacidal activity of this MAb was linked to interference with iron acquisition by C. albicans [78] (Fig.…”
Section: Demonstration Of Protective Role Of Antibodies In Fungal Infmentioning
confidence: 99%